2021
DOI: 10.1108/tpm-12-2020-0110
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence, voice and flow: a team-level study of work teams

Abstract: Purpose This paper aims to investigate how emotional intelligence and voice climate interact with flow in work teams. Design/methodology/approach The authors used multilevel structural equation modeling to analyze the nested data (individuals within teams). A total of 42 work teams (166 full-time employees) from the service industry participated in this research. Findings The results showed that emotional intelligence and voice behavior are positively associated with flow experience at the individual level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 88 publications
1
6
0
Order By: Relevance
“…The reported positive relationship between EI and flow proneness ( r = 0.39) in musicians aligns with a previous study on classical pianists [ 37 ] and bolsters foundational research in other domains, such as work [ 91 ] and education [ 92 ], which suggested an association between flow and EI warrants further exploration. Those with high EI may possess skills such as emotional management and emotional regulation [ 93 ], helping with flow proneness, but such coping mechanisms may be insufficient when individuals have high anxiety at clinical levels.…”
Section: Discussionsupporting
confidence: 88%
“…The reported positive relationship between EI and flow proneness ( r = 0.39) in musicians aligns with a previous study on classical pianists [ 37 ] and bolsters foundational research in other domains, such as work [ 91 ] and education [ 92 ], which suggested an association between flow and EI warrants further exploration. Those with high EI may possess skills such as emotional management and emotional regulation [ 93 ], helping with flow proneness, but such coping mechanisms may be insufficient when individuals have high anxiety at clinical levels.…”
Section: Discussionsupporting
confidence: 88%
“…As for individual factors, employees with a proactive personality or highly extraverted ones perceive voice as an opportunity to serve their interests and to achieve organizational goals [32,33]. Employees' abilities, such as communication competency and EQ, facilitate the exchange of ideas, leading to voice behavior [34,35].…”
Section: Employee Voicementioning
confidence: 99%
“…Structural equation modeling was a popular research method as well ( n = 9). However, we found only one study used multi-level structural equation modelling (MSEM) to analyze multi-level data (Xie et al , 2021). Regarding qualitative research, most scholars used traditional semi-structured interviews as their main source for research data (n = 11).…”
Section: Research Designsmentioning
confidence: 99%
“…Model- and design-based MSEM is more advantageous than regular multiple regression analysis with aggregated scores (Xie et al , 2021). If data are aggregated, much information is lost, and the statistical analysis loses power (Hox et al , 2017).…”
Section: Agenda For Future Critical Human Resource Development Researchmentioning
confidence: 99%
See 1 more Smart Citation